2018
DOI: 10.1016/j.hpb.2018.02.509
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition associated with postoperative complications in patients undergone hepatectomy for hepatocellular carcinoma

Abstract: Background: The factors affecting hypertrophy of the future liver remnant (FLR) after portal vein embolization (PVE) remain unclear. The aim of this study was to clarify the clinical factors affecting the hypertrophy rate after PVE and to develop a scoring system predicting insufficient liver hypertrophy. Methods: A total of 152 patients who underwent PVE of the right portal branch between 2006 and 2016 were reviewed retrospectively. The score to predict insufficient (<25%) hypertrophy was established based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…9,37 Huang et al found that malnourished patients based on the patient-generated subjective global assessment undergoing hepatectomy were found to be associated with more occurrences of major postoperative complications (CD grade C 3a). 38 Although postoperative infections contributed to the majority of postoperative complications (56.6%) in our study, we did not find a significant association between high MUST score and postoperative infections in our study. This is in contrast to other studies that found an association between preoperative malnutrition and increased postoperative infections.…”
Section: Discussioncontrasting
confidence: 78%
“…9,37 Huang et al found that malnourished patients based on the patient-generated subjective global assessment undergoing hepatectomy were found to be associated with more occurrences of major postoperative complications (CD grade C 3a). 38 Although postoperative infections contributed to the majority of postoperative complications (56.6%) in our study, we did not find a significant association between high MUST score and postoperative infections in our study. This is in contrast to other studies that found an association between preoperative malnutrition and increased postoperative infections.…”
Section: Discussioncontrasting
confidence: 78%